2021
DOI: 10.1002/pro.4091
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of novel monoclonal antibodies to human angiotensin I‐converting enzyme

Abstract: Angiotensin I-converting enzyme (ACE, CD143) plays a crucial role in blood pressure regulation, vascular remodeling, and immunity. A wide spectrum of mAbs to different epitopes on the N and C domains of human ACE have been generated and used to study different aspects of ACE biology, including establishing a novel approach-conformational fingerprinting. Here we characterized a novel set of 14 mAbs, developed against human seminal fluid ACE. The epitopes for these novel mAbs were defined using recombinant ACE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 51 publications
(172 reference statements)
0
22
0
Order By: Relevance
“…The power of our ACE fingerprinting approach to identify sarcoidosis “mimics” is further illustrated by other examples. As noted above, high levels of blood ACE can be caused by certain ACE mutations that increase shedding of the enzyme or its secretion from endothelial cells (reviewed in [ 28 ]). While ACE mutations that eliminate transmembrane anchoring [ 47 , 48 ] result in 14–20 fold increases in blood ACE and thus can be easily recognized, other ACE mutations that increase shedding and blood ACE levels by only four-sixfold [ 41 , 42 , 49 , 50 ] are much more likely to be incorrectly attributed to possible sarcoidosis, leading to unnecessary diagnostic procedures or treatment for these patients [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The power of our ACE fingerprinting approach to identify sarcoidosis “mimics” is further illustrated by other examples. As noted above, high levels of blood ACE can be caused by certain ACE mutations that increase shedding of the enzyme or its secretion from endothelial cells (reviewed in [ 28 ]). While ACE mutations that eliminate transmembrane anchoring [ 47 , 48 ] result in 14–20 fold increases in blood ACE and thus can be easily recognized, other ACE mutations that increase shedding and blood ACE levels by only four-sixfold [ 41 , 42 , 49 , 50 ] are much more likely to be incorrectly attributed to possible sarcoidosis, leading to unnecessary diagnostic procedures or treatment for these patients [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…During 30 years of intensive study of the ACE protein, we have generated a unique set of monoclonal antibodies (mAbs) to more than 40 different epitopes on the N-and C-domains of human ACE [26][27][28]. Localization of the epitopes of all these mAbs on the ACE molecule (epitope mapping) have allowed us to identify and map critical functional regions of this essential enzyme and to establish the novel approach for ACE studies-conformational fingerprinting of ACE [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although sACE glycosylation occurs to varying degrees in different tissues (Kryukova et al , 2015 ) the structural and functional relevance of this tissue specificity is unknown, but is important since it affects antibody binding and thus the diagnosis of diseases where sACE is upregulated (Danilov et al , 2010 , 2018 , 2021 ; Danilov, 2017 ). The present study paves the way for investigations into the detailed glycan structures of different sACE glycoforms using MD simulations along with comprehensive mass spectrometry analysis and will aid the development of monoclonal antibodies by allowing for enhanced epitope mapping (Popova et al , 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…This prediction agrees with our previous findings, where S357V and E431D mutations in Site 5 altered protein hinging and decreased N‐domain‐selective inhibitor binding to the orthosteric site (Lubbe et al , 2016 ). It is interesting to note that the Alzheimer's disease‐associated T887M mutation, which drastically reduces antibody binding (Sassi et al , 2016 ; Popova et al , 2021 ), is located on C‐domain hinge 4 near Site 8 and could thus alter hinging. In agreement with the predicted allosteric effects of hinge 2 and 4 from the present study, a strong N‐domain‐selective anticatalytic effect was previously observed upon binding of monoclonal antibody i2H5 to its epitope formed by Site 7 and hinge 4 (Skirgello et al , 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…5A) may be attributed to differential ACE glycosylation in the endothelial cells of the lung and in ACE-positive cells in frontal cortex of the brain (endothelial cells and neurons. 8,9 Speci c glycosylation sites in the ACE protein include Asn82 (localized in the epitopes for mAbs 3A5/3G8/5B3), Asn45 (mAbs 6C8/6H6/2D1) and perhaps Asn131 (epitope for mAb 2D7), Asn685 (epitope for mAbs 1E10/3C10/4E3/2H9), perhaps Asn913 (possibly in the epitope for mAb 8H1) and Asn1196 (epitope for mAb 4C12)-see epitope mapping previously described in 31 .…”
Section: Global Distribution and Age Of Ace Variantsmentioning
confidence: 99%